A phase change composite material and its preparation method and application

By preparing phase change composite materials with specific ratios, the problem of layering of existing phase change materials after repeated use is solved, and good cooling effect and service life are achieved.

CN119144158BActive Publication Date: 2025-02-14PHASE CHANGE ENERGY STORAGE (BEIJING) TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411659381.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Existing phase change materials are prone to stratification after repeated use, resulting in weakening of cooling effect and affecting the performance and service life of the product.

Method used

The phase change composite materials with specific ratios, including acrylate polymers, crosslinking agents, emulsifiers, solvents, initiators, phase change materials, thermal fillers, thickeners and stabilizers, are prepared by mixing and polymerization reactions. Material with good adhesion and flexibility.

Benefits of technology

The phase change composite material does not have layering after repeated use, maintains good cooling effect, and extends its service life. Its preparation method is simple, easy to operate and has high efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144158B_ABST
    Figure CN119144158B_ABST
Patent Text Reader

Abstract

The present invention discloses a phase change composite material and a preparation method and application thereof, belonging to the technical field of phase change materials. The raw materials for preparing the phase change composite material include 2 to 10 parts of acrylic polymer, 0.02 to 0.3 parts of cross-linking agent, 0.1 to 3 parts of emulsifier, 1 to 25 parts of solvent, 0.05 to 3 parts of initiator, 0.5 to 3 parts of acrylic monomer, 2 to 20 parts of phase change material, 0.5 to 3 parts of thermal conductive filler, 0.01 to 2.5 parts of thickener and 0.1 to 1 part of stabilizer. The phase change composite material has good adhesion and flexibility, and can be used repeatedly without stratification, so as to maintain a good cooling effect and extend the service life. The preparation method is simple, easy to operate and efficient. The phase change composite material can be used to adjust the temperature, for example, it can be used in a heat preservation container.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phase change materials, and in particular to a phase change composite material and a preparation method and application thereof. Background Art

[0002] At present, phase change materials are usually used to achieve temperature control. In some cases, phase change materials can be used in thermal insulation containers such as thermos cups, which can quickly reduce the temperature of the liquid in the cup to a certain extent and keep the liquid temperature constant. However, the current phase change material formula composition is relatively fixed, lacking the ability to flexibly adapt to different temperature control requirements, and technical difficulties in the filling process will affect production efficiency and product quality; more importantly, phase change materials will stratify after repeated use, resulting in a weakened cooling effect, affecting product performance and service life.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a phase change composite material and a preparation method and application thereof, so as to at least solve or improve the problem that the phase change material may delaminate after repeated use.

[0005] The present invention can be implemented like this:

[0006] In a first aspect, the present invention provides a phase change composite material. The raw materials for preparing the phase change composite material include, by weight, 2 to 10 parts of acrylic polymer, 0.02 to 0.3 parts of cross-linking agent, 0.1 to 3 parts of emulsifier, 1 to 25 parts of solvent, 0.05 to 3 parts of initiator, 0.5 to 3 parts of acrylic monomer, 2 to 20 parts of phase change material, 0.5 to 3 parts of thermal conductive filler, 0.01 to 2.5 parts of thickener and 0.1 to 1 part of stabilizer.

[0007] In an optional embodiment, the raw materials for preparing the phase change composite material include, by mass, 2 to 5 parts of the acrylic polymer, 0.03 to 0.15 parts of the cross-linking agent, 0.2 to 1.5 parts of the emulsifier, 15 to 23 parts of the solvent, 0.15 to 2 parts of the initiator, 1 to 2 parts of the acrylic monomer, 5 to 15 parts of the phase change material, 1 to 2 parts of the thermally conductive filler, 0.05 to 0.4 parts of the thickener and 0.1 to 0.4 parts of the stabilizer.

[0008] In an optional embodiment, the acrylic polymer includes at least one of polypropylene glycol methacrylate, polyethylene glycol methacrylate and polyethylene glycol dimethacrylate;

[0009] Or, the cross-linking agent includes at least one of trimethylolpropane trimethacrylate, ethylene glycol dimethacrylate, and tetraethylene glycol dimethacrylate;

[0010] Or, the emulsifier includes at least one of a paraffin emulsifier, polyoxyethylene stearate, and a polysiloxane-polyether copolymer;

[0011] or, the solvent comprises water;

[0012] or, the initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone (Irgacure 184), 2-hydroxy-2-methyl-1-phenylpropanone (such as Darocur 1173 or Irgacure 1173), 2,2-dimethoxy-2-phenylacetophenone (Irgacure 651), potassium persulfate, ammonium persulfate and benzoyl peroxide;

[0013] Or, the acrylic acid ester monomer includes at least one of lauryl acrylate and octadecyl acrylate;

[0014] Or, the phase change material includes at least one of paraffin, fatty acid, fatty alcohol and fatty ester;

[0015] Alternatively, the thermally conductive filler includes at least one of alumina, boron nitride, expanded graphite, graphene, and carbon nanotubes.

[0016] Alternatively, the thickener includes at least one of polyethylene oxide, carboxymethyl cellulose and xanthan gum.

[0017] Alternatively, the stabilizer includes at least one of glycerol, polyacrylic acid, polyethylene glycol and urea.

[0018] In an optional embodiment, in the phase change material, the fatty acid includes at least one of myristic acid, palmitic acid, margaric acid and stearic acid; or, the fatty alcohol includes at least one of stearyl alcohol, nonadecanol, arachidyl alcohol, behenyl alcohol and wax alcohol; or, the fatty ester includes at least one of methyl lignocerate, methyl wax ester, methyl heptadecanoate, methyl octadecanoate, methyl stearate and ethyl stearate.

[0019] In a second aspect, the present invention provides a method for preparing a phase change composite material as described in any one of the aforementioned embodiments, comprising the following steps: mixing and reacting various raw materials of the phase change composite material according to a proportion.

[0020] In an optional embodiment, the preparation process includes: mixing an emulsifier and a phase change material, and adding the mixture dropwise into a solvent to obtain an emulsion; mixing the emulsion with a prepolymer to obtain a mixed liquid, wherein the components of the prepolymer include an acrylic polymer, a cross-linking agent, an acrylic monomer, a thickener, and a stabilizer; mixing an initiator and a thermally conductive filler with the mixed liquid and performing a polymerization reaction.

[0021] In an optional embodiment, the polymerization includes any one of thermal polymerization and UV polymerization;

[0022] The polymerization temperature corresponding to the thermal polymerization is 60°C to 80°C, and the polymerization time is 0.5h to 4h.

[0023] The UV intensity corresponding to UV polymerization is 10mW / cm²~100mW / cm², and the polymerization reaction time is 100s~1800s.

[0024] In a third aspect, the present invention provides an application of the phase change composite material according to any one of the aforementioned embodiments, for example, for regulating temperature.

[0025] In a fourth aspect, the present invention provides a thermal insulation container, wherein a structural layer of the thermal insulation container contains the phase change composite material of any one of the aforementioned embodiments.

[0026] In an optional embodiment, the thermal insulation container is a thermal insulation cup, which has an interlayer, and the interlayer is filled with the above-mentioned phase change composite material along the circumference of the thermal insulation container.

[0027] The beneficial effects of the present invention include:

[0028] The phase change composite material obtained by the specific raw materials and specific ratios provided by the present invention has good adhesion and flexibility, and can maintain good cooling effect and extend service life without stratification after repeated use. The preparation method is simple, easy to operate and efficient. The phase change composite material can be used to adjust the temperature, for example, it can be used in a heat preservation container. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0030] Figure 1 This is a graph showing the corresponding physical result after the viscosity test of the phase change composite material prepared in Example 1 of the present invention;

[0031] Figure 2 This is a diagram showing the actual results of the phase change composite material prepared in Example 1 of the present invention after the flexibility test is carried out;

[0032] Figure 3 The graphs are the corresponding physical result diagrams after the stratification test of the phase change composite materials prepared in Examples 1 to 7 of the present invention and the competing products. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] The phase change composite material provided by the present invention and its preparation method and application are described in detail below.

[0035] The present invention provides a phase change composite material. The raw materials for preparing the phase change composite material include, by weight, 2 to 10 parts of acrylic polymer, 0.02 to 0.3 parts of cross-linking agent, 0.1 to 3 parts of emulsifier, 1 to 25 parts of solvent, 0.05 to 3 parts of initiator, 0.5 to 3 parts of acrylic monomer, 2 to 20 parts of phase change material, 0.5 to 3 parts of thermal conductive filler, 0.01 to 2.5 parts of thickener and 0.1 to 1 part of stabilizer.

[0036] The acrylic polymer is mainly used to provide flexibility. The acrylic polymer may illustratively but not limitatively include at least one of polypropylene glycol methacrylate (PPGMA), polyethylene glycol methacrylate (PEGMA) and polyethylene glycol dimethacrylate (PEGDA).

[0037] For example, the amount of acrylic polymer in the phase change composite material can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts or 10 parts, etc., or other values ​​within the range of 2 parts to 10 parts.

[0038] By using the above-mentioned acrylic polymer and controlling its dosage within the range of 2 to 10 parts, the phase change composite material can have appropriate flexibility after being combined with other raw materials. If the dosage of acrylic polymer is inappropriate, the phase change composite material will be unformed or too hard. Among them, the unformed material may appear loose and amorphous, or cannot be cured into the designed shape during the processing, and it is difficult to maintain the integrity of the structure; too hard will break or shatter under bending conditions.

[0039] The crosslinking agent is mainly used to achieve chemical crosslinking of acrylic polymers and acrylic monomers. The crosslinking agent may exemplarily but not limitatively include at least one of trimethylolpropane trimethacrylate (TRIM), ethylene glycol dimethacrylate (EGDMA) and tetraethylene glycol dimethacrylate (TEGDMA).

[0040] For example, the amount of the crosslinking agent in the phase change composite material can be 0.02 parts, 0.03 parts, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts or 0.3 parts, etc., or other values ​​within the range of 0.02 parts to 0.3 parts.

[0041] By using the above cross-linking agent and controlling its dosage within the range of 0.02 to 0.3 parts, the phase change composite material can have a suitable viscosity after being matched with other raw materials, and the corresponding phase change composite material can form a three-dimensional network structure, improve the structural stability of the phase change composite material, thereby helping to avoid or improve the stratification problem that is easily caused by repeated use of the phase change composite material, thereby maintaining a good cooling effect, and effectively keeping warm after cooling to a certain temperature range, extending the service life. If the amount of cross-linking agent is too much, it is easy to cause the viscosity of the phase change composite material to be too low, and it is difficult to adhere to the surface of the insulation container.

[0042] The above-mentioned emulsifier is mainly used to improve the mutual solubility between the raw materials (such as phase change material and solvent water). The emulsifier can exemplarily but not limitatively include at least one of paraffin emulsifier, polyoxyethylene stearate and polysiloxane-polyether copolymer. Among them, the polysiloxane-polyether copolymer can include at least one of polyoxyethylene methylsiloxane, polydimethylsiloxane-polyoxyethylene copolymer and polyoxyethylene polyoxypropylene copolymer dimethylsiloxane.

[0043] For example, the amount of emulsifier used in the phase change composite material can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts, etc., or other values ​​within the range of 0.1 part to 3 parts.

[0044] By using the above emulsifier and controlling its dosage within the range of 0.1 to 3 parts, the phase change composite material system can be made more uniform and stable after being combined with other raw materials.

[0045] The above solvent may be water.

[0046] For example, the amount of solvent in the phase change composite material can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts or 25 parts, etc., or other values ​​within the range of 1 part to 25 parts. Within this amount range, the phase change composite material can have a more suitable viscosity. If the amount of water is too much, the viscosity of the phase change composite material will be too low.

[0047] The initiator is mainly used to initiate the crosslinking reaction. The initiator may exemplarily but not limitatively include at least one of 1-hydroxycyclohexyl phenyl ketone (Irgacure 184), 2-hydroxy-2-methyl-1-phenylpropanone (such as Darocur 1173 or Irgacure 1173), 2,2-dimethoxy-2-phenylacetophenone (Irgacure 651), potassium persulfate, ammonium persulfate and benzoyl peroxide.

[0048] For example, the amount of initiator used in the phase change composite material can be 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts, etc., or other values ​​within the range of 0.05 parts to 3 parts.

[0049] By using the above-mentioned initiator and controlling its dosage within the range of 0.05 to 3 parts, the polymerization reaction of the phase change composite material can be effectively carried out after being matched with other raw materials. If the dosage of the initiator is too small, the polymerization reaction will be incomplete and stratification will occur; if the dosage of the initiator is too large, it is easy to cause the sample to harden and produce precipitates.

[0050] The acrylic acid ester monomer may illustratively but not limitatively include at least one of lauryl acrylate and octadecyl acrylate.

[0051] As an example, the amount of acrylate monomers in the phase change composite material can be 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts, etc., or other values ​​within the range of 0.5 parts to 3 parts. Within the above range, as the amount of acrylate monomers increases, the viscosity of the phase change composite material increases. However, if the amount of acrylate monomers exceeds the above range, a dense cross-linked network will be formed, resulting in an increase in the hardness and brittleness of the composite material, limiting the flexibility and elasticity of the material, which is not conducive to practical applications.

[0052] The above phase change material mainly plays the role of regulating temperature. The phase change material may exemplarily but not limitatively include at least one of paraffin, fatty acid, fatty alcohol and fatty ester. Among them, the fatty acid may include at least one of myristic acid, palmitic acid, heptadecanoic acid and stearic acid; the fatty alcohol may include at least one of stearyl alcohol, nonadecanol, arachidyl alcohol, behenyl alcohol and fatty wax alcohol; the fatty ester may include at least one of methyl lignocerate, methyl wax ester, methyl heptadecanoate, methyl octadecanoate, methyl stearate and ethyl stearate.

[0053] For example, the amount of phase change material in the phase change composite material can be 2 parts, 3 parts, 4 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts or 20 parts, etc., or other values ​​within the range of 2 parts to 20 parts.

[0054] The thermally conductive filler can conduct heat, and can include, by way of example but not limitation, at least one of aluminum oxide, boron nitride, expanded graphite, graphene, and carbon nanotubes.

[0055] For example, the amount of thermally conductive filler in the phase change composite material can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts, etc., or other values ​​within the range of 0.5 parts to 3 parts.

[0056] By adopting the above-mentioned phase change material and thermal conductive filler and controlling their usage in the range of 2 to 20 parts and 0.5 to 3 parts respectively, the phase change composite material can have a rapid cooling effect after being combined with other raw materials, and can maintain temperature stability for a long time after cooling to a suitable temperature.

[0057] The thickener mentioned above mainly plays a role of thickening, and the thickener may illustratively but not limitatively include at least one of polyethylene oxide, carboxymethyl cellulose and xanthan gum.

[0058] For example, the amount of thickener used can be 0.01 parts, 0.05 parts, 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts or 2.5 parts, etc., and can also be other values ​​within the range of 0.01 parts to 2.5 parts.

[0059] The stabilizer mentioned above mainly plays a stabilizing role, and the stabilizer may illustratively but not limitatively include at least one of glycerol, polyacrylic acid, polyethylene glycol and urea.

[0060] For example, the amount of the stabilizer can be 0.1 part, 0.2 part, 0.5 part, 0.8 part or 1 part, etc., or other values ​​within the range of 0.1 part to 2 parts.

[0061] In some preferred embodiments, the raw materials for preparing the phase change composite material include, by weight, 2 to 5 parts of acrylic polymer, 0.03 to 0.15 parts of cross-linking agent, 0.2 to 1.5 parts of emulsifier, 15 to 23 parts of solvent, 0.15 to 2 parts of initiator, 1 to 2 parts of acrylic monomer, 5 to 15 parts of phase change material, 1 to 2 parts of thermal conductive filler, 0.05 to 0.4 parts of thickener and 0.1 to 0.4 parts of stabilizer.

[0062] As mentioned above, the phase change composite material provided by the present invention can adapt to different temperature control requirements. It has good adhesion and can be tightly attached to the surface of the structural layer (such as the inner layer) of the insulation container (such as the insulation cup), which is conducive to improving the practicality and convenience of the product; and the phase change composite material also has good flexibility and can maintain the integrity of the structure at different temperatures. In addition, the phase change composite material provided by the present invention can also reduce or avoid the occurrence of stratification after repeated use, so as to maintain a good cooling effect. After cooling to a certain temperature range, it can effectively keep warm and extend the service life.

[0063] Correspondingly, the present invention also provides a method for preparing the above phase change composite material, comprising the following steps: mixing and reacting various raw materials of the phase change composite material according to a proportion.

[0064] In some embodiments, the preparation process includes: mixing an emulsifier and a phase change material, and adding the mixture dropwise into a solvent to obtain an emulsion; mixing the emulsion with a prepolymer to obtain a mixed liquid, wherein the components of the prepolymer include an acrylic polymer, a cross-linking agent, an acrylic monomer, a thickener, and a stabilizer; mixing an initiator and a thermally conductive filler with the mixed liquid and performing a polymerization reaction.

[0065] Specifically, the emulsifier and the phase change material can be mixed and then added dropwise to the solvent to form a uniform emulsion; acrylic polymer, crosslinking agent, acrylic monomer, thickener and stabilizer are added to the above emulsion, and a homogenizer is used to mix them at high speed (such as 100r / min~5000r / min) until a uniform mixed liquid is formed; then the initiator and the thermal conductive filler are added to the mixed liquid, and a homogenizer is used to mix them at low speed (such as 500r / min~1000r / min) to carry out a polymerization reaction.

[0066] By following the above-mentioned specific mixing order, the phase change composite material can have a better anti-stratification effect. Among them, the emulsifier and the phase change material are first mixed and then added dropwise to the solvent, so that the phase change material can be evenly dispersed in the solvent, ensuring the uniformity of the phase change material in the final composite material. On this basis, a uniform mixed liquid is first formed with materials such as acrylic polymers, and then an initiator and a thermally conductive filler are added. Part of the emulsion is adsorbed in the pore structure of the thermally conductive filler, which plays a physical adsorption role. The initiator then initiates a polymerization reaction to achieve chemical crosslinking. In this way, the structural stability of the material is further improved and the risk of stratification is reduced.

[0067] In some embodiments, the polymerization includes any one of thermal polymerization and UV polymerization.

[0068] When thermal polymerization is adopted, the polymerization reaction temperature can be 60°C to 80°C, such as 60°C, 65°C, 70°C, 75°C or 80°C, etc., or other values ​​within the range of 60°C to 80°C. The polymerization reaction time can be 0.5h to 4h, such as 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h, etc., or other values ​​within the range of 0.5h to 4h.

[0069] When UV polymerization is adopted, the UV intensity corresponding to the UV polymerization can be 10mW / cm²~100mW / cm², such as 10mW / cm², 20mW / cm², 40mW / cm², 60mW / cm², 80mW / cm² or 100mW / cm², etc., or other values ​​within the range of 10mW / cm²~100mW / cm².

[0070] The time of the UV polymerization reaction may be 100 s to 1800 s, such as 100 s, 200 s, 500 s, 800 s, 1000 s, 1200 s, 1400 s, 1600 s or 1800 s, or other values ​​within the range of 100 s to 1800 s.

[0071] Thermal polymerization is suitable for the preparation of phase change composite materials with high molecular weight, high temperature resistance and excellent thermal conductivity, while UV polymerization is suitable for systems containing heat-sensitive materials or situations where rapid polymerization is required.

[0072] As mentioned above, the preparation method provided by the present invention is relatively simple, easy to operate and highly efficient.

[0073] In addition, the present invention also provides an application of the phase change composite material, for example, for regulating temperature, and further for regulating water temperature.

[0074] Correspondingly, the present invention also provides a heat-insulating container, the structural layer of which contains the above-mentioned phase-change composite material.

[0075] As an example, the thermal insulation container is a thermal insulation cup, which has an interlayer, and the interlayer is filled with the above-mentioned phase change composite material along the circumference of the thermal insulation container.

[0076] Exemplarily, along the circumference of the thermos cup, the phase change composite material is evenly spread on the surface of the interlayer.

[0077] In some embodiments, the mass of the liquid contained in the thermos cup may be 3.5 to 4 times the mass of the phase change composite material contained in the interlayer.

[0078] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0079] Example 1

[0080] This embodiment provides a phase change composite material, the material of which is as follows Figure 1 and Figure 2 As shown, Figure 1 The amount of phase change composite materials is greater. Figure 2 The amount of phase change material is even less.

[0081] Measured by mass (each portion = 1 g), the raw materials for preparing the phase change material include 2 g of acrylic acid ester polymer (PEGMA), 0.03 g of cross-linking agent (EGDMA), 0.2 g of emulsifier (paraffin emulsifier), 22 g of water, 0.15 g of initiator (ammonium persulfate), 1 g of acrylic acid ester monomer (octadecyl acrylate), 15 g of phase change material (paraffin), 1 g of thermal conductive filler (expanded graphite), 0.2 g of thickener (polyethylene oxide) and 0.2 g of stabilizer (glycerol).

[0082] The preparation of the phase change composite material comprises:

[0083] S1: The emulsifier and the phase change material were mixed according to the ratio, and the mixture was added dropwise into water, and mixed thoroughly using a homogenizer at 2000 rpm until a stable emulsion was formed.

[0084] S2: PEGMA, EGDMA, acrylic ester monomers, thickeners and stabilizers were added to the emulsion, and the mixture was fully mixed at 2000 rpm for 5 min using a homogenizer to obtain a mixed solution.

[0085] S3: adding an initiator and expanded graphite to the mixed solution, fully mixing with a homogenizer at 750 rpm, and performing a polymerization reaction at 80° C. for 1 h to obtain a phase change composite material.

[0086] Example 2

[0087] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by mass (each portion = 1 g), 2 g of an acrylate polymer (PEGMA), 0.03 g of a cross-linking agent (EGDMA), 0.2 g of an emulsifier (paraffin emulsifier), 22 g of water, 0.15 g of an initiator (ammonium persulfate), 1 g of an acrylate monomer (octadecyl acrylate), 15 g of a phase change material (paraffin), 1 g of a thermally conductive filler (graphene), 0.2 g of a thickener (polyethylene oxide) and 0.2 g of a stabilizer (glycerol).

[0088] That is, the difference between this embodiment and embodiment 1 is that the thermal conductive filler is changed, and expanded graphite is replaced by graphene.

[0089] The preparation steps and conditions of the phase change composite material are the same as those in Example 1.

[0090] Example 3

[0091] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by mass (each portion = 1 g), 2 g of an acrylic polymer (PPGMA), 0.03 g of a cross-linking agent (TRIM), 0.2 g of an emulsifier (paraffin emulsifier), 22 g of water, 0.15 g of an initiator (potassium persulfate), 1 g of an acrylic monomer (lauryl acrylate), 15 g of a phase change material (stearic acid), 1 g of a thermally conductive filler (graphene), 0.2 g of a thickener (carboxymethyl cellulose) and 0.2 g of a stabilizer (polyethylene glycol).

[0092] Example 4

[0093] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by mass (each portion = 1 g), 2 g of an acrylate polymer (PEGDA), 0.03 g of a cross-linking agent (TEGDMA), 0.2 g of an emulsifier (paraffin emulsifier), 22 g of water, 0.15 g of an initiator (potassium persulfate), 1 g of an acrylate monomer (octadecyl acrylate), 15 g of a phase change material (stearyl alcohol), 1 g of a thermally conductive filler (expanded graphite), 0.2 g of a thickener (xanthan gum) and 0.2 g of a stabilizer (urea).

[0094] Example 5

[0095] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by mass parts (each part = 1 g), 5 g of an acrylic polymer (PEGMA), 0.15 g of a cross-linking agent (EGDMA), 0.6 g of an emulsifier (paraffin emulsifier), 23 g of water, 0.15 g of an initiator (ammonium persulfate), 1.5 g of an acrylic monomer (octadecyl acrylate), 5 g of a phase change material (paraffin), 1.5 g of a thermally conductive filler (expanded graphite), 0.05 g of a thickener (polyethylene oxide), and 0.1 g of a stabilizer (glycerol).

[0096] Example 6

[0097] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by mass parts (each part = 1 g), 3.5 g of an acrylate polymer (PEGMA), 0.05 g of a cross-linking agent (EGDMA), 1.5 g of an emulsifier (paraffin emulsifier), 15 g of water, 0.05 g of an initiator (ammonium persulfate), 2 g of an acrylate monomer (octadecyl acrylate), 8 g of a phase change material (paraffin), 2 g of a thermally conductive filler (expanded graphite), 0.4 g of a thickener (polyethylene oxide) and 0.4 g of a stabilizer (glycerol).

[0098] Example 7

[0099] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by mass (each portion = 1 g), 10 g of an acrylic polymer (PEGMA), 0.3 g of a cross-linking agent (EGDMA), 3 g of an emulsifier (paraffin emulsifier), 25 g of water, 3 g of an initiator (ammonium persulfate), 3 g of an acrylic monomer (octadecyl acrylate), 20 g of a phase change material (paraffin), 3 g of a thermally conductive filler (expanded graphite), 2.5 g of a thickener (polyethylene oxide), and 1 g of a stabilizer (glycerol).

[0100] Example 8

[0101] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by mass parts (each part = 1 g), 4 g of an acrylate polymer (PEGMA), 0.02 g of a cross-linking agent (EGDMA), 0.7 g of an emulsifier (paraffin emulsifier), 1 g of water, 0.15 g of an initiator (ammonium persulfate), 1 g of an acrylate monomer (octadecyl acrylate), 2 g of a phase change material (paraffin), 1 g of a thermally conductive filler (expanded graphite), 0.01 g of a thickener (polyethylene oxide) and 0.1 g of a stabilizer (glycerol).

[0102] Example 9

[0103] The present embodiment provides a phase change composite material. The raw materials for preparing the phase change material include, by weight (each part = 1 g), 5 g of an acrylate polymer (PEGMA), 0.15 g of a cross-linking agent (EGDMA), 1.5 g of an emulsifier (paraffin emulsifier), 22 g of water, 2 g of an initiator (Irgacure 1173), 2 g of an acrylate monomer (octadecyl acrylate), 12 g of a phase change material (paraffin), 0.5 g of a thermally conductive filler (expanded graphite), 0.2 g of a thickener (polyethylene oxide), and 0.2 g of a stabilizer (glycerol).

[0104] The difference between this embodiment and embodiment 1 is that the initiator and curing method are changed. Specifically, step S4 is: adding the initiator and expanded graphite to the emulsion, and performing polymerization reaction in a UV box for 600 seconds to obtain a phase change composite material.

[0105] Comparative Example 1

[0106] This comparative example provides a phase change composite material (such as Figure 3As shown in the figure, the phase change material includes, by mass (each portion = 1 g), 2 g of an acrylic polymer (PEGMA), 0.03 g of a cross-linking agent (EGDMA), 4 g of water, 0.05 g of an initiator (ammonium persulfate), 1 g of an acrylic monomer (octadecyl acrylate), 15 g of a phase change material (paraffin), 1 g of a thermally conductive filler (expanded graphite), 0.2 g of a thickener (polyethylene oxide) and 0.2 g of a stabilizer (glycerol).

[0107] That is, the difference between this comparative example and Example 1 is that the raw materials for preparing the phase change composite material do not contain an emulsifier.

[0108] The preparation steps and conditions of the phase change composite material are substantially the same as those of Example 1, except that no emulsifier is added to S1.

[0109] Comparative Example 2

[0110] This comparative example provides a phase change composite material, which includes, by mass (each portion = 1 g), 2 g of an acrylate polymer (PEGMA), 0.03 g of a cross-linking agent (EGDMA), 0.2 g of an emulsifier (paraffin emulsifier), 4 g of water, 0.05 g of an initiator (ammonium persulfate), 1 g of an acrylate monomer (octadecyl acrylate), 15 g of a phase change material (paraffin), 0.2 g of a thickener (polyethylene oxide) and 0.2 g of a stabilizer (glycerol).

[0111] That is, the difference between this comparative example and Example 1 is that the raw materials for preparing the phase change composite material do not contain thermal conductive filler.

[0112] The preparation steps and conditions of the phase change composite material are substantially the same as those of Example 1, except that no thermal conductive filler is added to S3.

[0113] Comparative Example 3

[0114] This comparative example uses traditional materials purchased as phase change materials for comparison. The traditional materials are specifically phase change materials made of paraffin, graphite and a cross-linking agent (dimethoxymethane) in a mass ratio of 9:0.5:0.5.

[0115] Comparative Example 4

[0116] The difference between this comparative example and Example 1 is that the preparation raw materials only contain phase change material and thermal conductive material.

[0117] Comparative Example 5

[0118] The difference between this comparative example and Example 1 is that the amount of the acrylic acid ester polymer used is 1 g.

[0119] Comparative Example 6

[0120] The difference between this comparative example and Example 1 is that the amount of the acrylic acid ester polymer used is 12 g.

[0121] Comparative Example 7

[0122] The difference between this comparative example and Example 1 is that the amount of the cross-linking agent used is 0.5 g.

[0123] Comparative Example 8

[0124] The difference between this comparative example and Example 1 is that the amount of the solvent used is 30 g.

[0125] Comparative Example 9

[0126] The difference between this comparative example and Example 1 is that the amount of initiator used is 3.5 g.

[0127] Comparative Example 10

[0128] The difference between this comparative example and Example 1 is that the amount of the acrylic acid ester monomer used is 4 g.

[0129] Comparative Example 11

[0130] The difference between this comparative example and Example 1 is that all the materials are mixed and prepared at the same time.

[0131] Comparative Example 12

[0132] The difference between this comparative example and Example 1 is that the order of adding the substances is different. The preparation of the phase change composite material includes:

[0133] S1: PEGMA, EGDMA, acrylate monomers and phase change materials were uniformly mixed according to the proportion, and fully mixed using a homogenizer at 2000 rpm to obtain an oil phase.

[0134] S2: The thickener, stabilizer, solvent and emulsifier are mixed uniformly, and fully mixed using a homogenizer at 2000 rpm to obtain an aqueous phase.

[0135] S3: Drop the oil phase into the water phase and use a homogenizer to stir at 6000 rpm for 10 min until the oil phase is fully dispersed into an emulsion.

[0136] S4: adding an initiator and expanded graphite to the mixed solution, fully mixing with a homogenizer at 750 rpm, and performing a polymerization reaction at 80° C. for 1 h to obtain a phase change composite material.

[0137] Test example

[0138] ①. The phase change composite materials of Examples 1 to 9 and Comparative Examples 1 to 12 were tested for viscosity and flexibility, wherein the viscosity test method was as follows: take a material sample of about 2 cm × 2 cm, spread it evenly on a glass plate and keep it for 5 seconds. Then, use a dynamometer to pull the sample horizontally, and record the initial adhesion force required to pull the sample. Flexibility test method: Use a standard sample mold to prepare a sample strip of 10 cm × 2 cm × 1 cm. Gradually apply force until the sample is bent to 45°, and record the bending strength during the bending process. The results are shown in Table 1.

[0139] Among them, taking Example 1 as an example, the actual results corresponding to the viscosity test are as follows Figure 1 The actual results of the flexibility test are shown in Figure 2 shown.

[0140] Depend on Figure 1 It can be seen that the phase change composite material prepared in Example 1 has good viscosity; Figure 2 It can be seen that the phase change composite material prepared in Example 1 has good flexibility.

[0141] ②. The phase change composite materials of Examples 1 to 9 and Comparative Examples 1 to 12 were subjected to a delamination test. The specific method is as follows: the phase change composite material was phase-changed 50 times, and the phase change conditions were as follows: the material was heated to 90°C, and after the material was completely melted, the material was cooled to 30°C, and the material was completely phase-changed. Whether the phase change material was delaminated was observed, and the results are shown in Table 1.

[0142] In addition, a commercially available phase change composite material (referred to as "competitor") was used as a comparison, and its phase change stratification is as follows: Figure 3 shown.

[0143] Depend on Figure 3 It can be clearly seen that the competing products have delamination, while the phase change composite materials prepared in Examples 1 to 7 of the present invention have no delamination.

[0144] ③. The phase change composite materials of Examples 1 to 9 and Comparative Examples 1 to 12 were filled into the interlayer of a thermos cup of the same size and specification in the same filling amount and filling method, and the cooling rate of the water in the thermos cup was compared. The results are shown in Table 1.

[0145] Table 1 Test results

[0146]

[0147] As can be seen from Table 1, the phase change composite materials prepared in Examples 1 to 9 all have good adhesion and can be tightly attached to the surface of the inner layer of the thermos cup. In addition, the phase change composite materials prepared in Examples 1 to 9 all have sufficient flexibility and can maintain their structural integrity at different temperatures. In addition, after the phase change composite materials prepared in Examples 1 to 9 were repeatedly phase-changed 50 times, there was no stratification phenomenon and the water could have a faster cooling rate.

[0148] The phase change composite materials prepared in Comparative Examples 1 to 12 are hard, have no adhesion and flexibility at room temperature, have stratification after heating, and have a low cooling rate of water.

[0149] The effects of Comparative Examples 11 to 12 are worse than those of Example 1, indicating that the preparation method also affects the performance of the material. The effects of Comparative Examples 1 to 10 are worse than those of Example 1, indicating that improper preparation of raw materials or improper ratio of raw materials will lead to poor material performance.

[0150] In summary, the phase change composite material provided by the present invention can adapt to different temperature control requirements. The phase change composite material has good adhesion and flexibility, and can maintain a good cooling effect without stratification after repeated use. After cooling to a certain temperature, it can effectively keep warm and extend the service life. The preparation method is simple, easy to operate, and efficient. The phase change composite material can be used to adjust the temperature, for example, it can be used in a heat-insulating container.

[0151] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A phase change composite material, characterized in that: The raw materials for preparing the phase change composite material include, by weight, 2 to 10 parts of acrylic polymer, 0.02 to 0.3 parts of cross-linking agent, 0.1 to 3 parts of emulsifier, 1 to 25 parts of solvent, 0.05 to 3 parts of initiator, 0.5 to 3 parts of acrylic monomer, 2 to 20 parts of phase change material, 0.5 to 3 parts of thermal conductive filler, 0.01 to 2.5 parts of thickener and 0.1 to 1 part of stabilizer; The acrylic polymer is selected from at least one of polypropylene glycol methacrylate, polyethylene glycol methacrylate and polyethylene glycol dimethacrylate; The acrylic acid ester monomer is selected from at least one of lauryl acrylate and octadecyl acrylate; The phase change material is selected from at least one of paraffin, fatty acid, fatty alcohol and fatty ester; The thermally conductive filler is selected from at least one of alumina, boron nitride, expanded graphite, graphene and carbon nanotubes; The preparation method of the phase change composite material comprises the following steps: mixing the emulsifier and the phase change material according to a ratio, and dropping the mixture into the solvent to obtain an emulsion; mixing the emulsion with a prepolymer to obtain a mixed liquid, wherein the prepolymer comprises the acrylic polymer, the crosslinking agent, the acrylic monomer, the thickener and the stabilizer; mixing the initiator and the thermal conductive filler with the mixed liquid and performing a polymerization reaction; The phase change composite material is used for cooling and heat preservation of heat preservation containers.

2. The phase change composite material according to claim 1, characterized in that: In terms of parts by mass, the raw materials for preparing the phase change composite material include 2 to 5 parts of the acrylic polymer, 0.03 to 0.15 parts of the cross-linking agent, 0.2 to 1.5 parts of the emulsifier, 15 to 23 parts of the solvent, 0.15 to 2 parts of the initiator, 1 to 2 parts of the acrylic monomer, 5 to 15 parts of the phase change material, 1 to 2 parts of the thermal conductive filler, 0.05 to 0.4 parts of the thickener and 0.1 to 0.4 parts of the stabilizer.

3. The phase change composite material according to claim 1 or 2, characterized in that: The cross-linking agent includes at least one of trimethylolpropane trimethacrylate, ethylene glycol dimethacrylate and tetraethylene glycol dimethacrylate; Or, the emulsifier includes at least one of a paraffin emulsifier, polyoxyethylene stearate, and a polysiloxane-polyether copolymer; or, the solvent comprises water; Or, the initiator includes at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 2,2-dimethoxy-2-phenylacetophenone, potassium persulfate, ammonium persulfate and benzoyl peroxide; Or, the thickener includes at least one of polyethylene oxide, carboxymethyl cellulose and xanthan gum; Alternatively, the stabilizer includes at least one of glycerol, polyacrylic acid, polyethylene glycol and urea.

4. The phase change composite material according to claim 1, characterized in that: In the phase change material, the fatty acid includes at least one of myristic acid, palmitic acid, margaric acid and stearic acid; or, the fatty alcohol includes at least one of stearyl alcohol, nonadecanol, arachidyl alcohol, behenyl alcohol and wax alcohol; or, the fatty ester includes at least one of methyl lignocerate, methyl wax ester, methyl heptadecanoate, methyl octadecanoate, methyl stearate and ethyl stearate.

5. A method for preparing the phase change composite material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the emulsifier and the phase change material according to a ratio, and dropping the mixture into the solvent to obtain an emulsion; mixing the emulsion with a prepolymer to obtain a mixed liquid, wherein the prepolymer comprises the acrylic polymer, the crosslinking agent, the acrylic monomer, the thickener and the stabilizer; and mixing the initiator and the thermal conductive filler with the mixed liquid to carry out a polymerization reaction.

6. The preparation method according to claim 5, characterized in that: The polymerization includes any one of thermal polymerization and ultraviolet polymerization; The polymerization temperature corresponding to the thermal polymerization is 60°C to 80°C, and the polymerization time is 0.5h to 4h. The UV intensity corresponding to UV polymerization is 10mW / cm²~100mW / cm², and the polymerization reaction time is 100s~1800s.

7. An application of the phase change composite material according to any one of claims 1 to 4, characterized in that: The phase change composite material is used for cooling and heat preservation of heat preservation containers.

8. A heat-insulating container, characterized in that: The structural layer of the thermal insulation container contains the phase change composite material according to any one of claims 1 to 4.

9. The heat-insulating container according to claim 8, characterized in that: The heat-insulating container is a heat-insulating cup, which has an interlayer, and the interlayer is filled with the phase-change composite material along the circumference of the heat-insulating container.

Citation Information

Patent Citations

  • Composite phase change material, application method thereof, and battery

    CN111793471A